The use of references: A study among Indonesian and Cambodian students in writing a research project - Ira Maisarah; Soeurn Chenda; Seth Soy (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2026)
The problem of this study was that university students are required to complete research projects as part of the course, such as theses or academic reports, to demonstrate their academic literacy. However, creating a well-structured academic report can sometimes be challenging for University of Bengkulu Master of English Language Education (MELE) Program students, especially when it comes to using appropriate referencing conventions. This was aimed at identifying the challenges MELE students face when writing a reference for a research report. The study used a qualitative, longitudinal research design for one semester. All MELE students enrolled in courses were taken as the population. Through voluntary participation, a sample of twenty-five students was chosen. Of the twenty-five students, six were international students from Cambodia. Two procedures were used to gather the data. First, document analysis of their research reports to find formatting errors in reference lists and in-text citations. Second, open-ended interviews. This interview was used to investigate students' perceptions, especially regarding challenges in writing. The results showed that students often challenged the international academic writing standards, maintaining consistency in reference formatting and accurately citing sources. Students from Cambodia and Indonesia both faced language barriers and challenges comprehending the typical format of research reports. Furthermore, a lack of knowledge or competence in using reference management became an issue. So, it suggests that to improve academic writing competence, systematic, ongoing guidance should be provided. For example, providing academic writing instruction, especially in teaching citation styles and the use of reference management software.